Hypoplasia of dopaminergic neurons by hypoxia-induced neurotoxicity is associated with disrupted swimming development of larval zebrafish - Son, Jong-Hyun; Gerenza, Amanda K.; Bingener, Gabrielle M.; Bonkowsky, Joshua L. (Frontiers in Cellular Neuroscience, 2022)
Hypoxic injury to the developing brain increases the risk of permanent behavioral deficits, but the precise mechanisms of hypoxic injury to the developing nervous system are poorly understood. In this study, we characterized the effects of developmental hypoxia (1% pO2 from 24-48 hours post-fertilization, hpf) on diencephalic dopaminergic (DA) neurons in larval zebrafish and the consequences on the development of swimming behavior. Hypoxia reduced the number of diencephalic DA neurons at 48hpf. Returning zebrafish larvae to normoxia after the hypoxia (i.e., hypoxia-recovery, HR) induced reactive oxygen species (ROS) accumulation. Real-time qPCR results showed that HR caused upregulation of proapoptotic genes, including p53 and caspase3, suggesting the potential for ROS-induced cell death. With HR, we also found an increase in TUNEL-positive dopaminergic DA neurons, a persistent reduction in the number of diencephalic DA neurons, and disrupted swimming development and behavior. Interestingly, post-hypoxia (HR) with the antioxidant N-acetylcysteine partially restored the number of DA neurons and spontaneous swimming behavior, demonstrating potential recovery from hypoxic injury. The present study provides new insights for understanding the mechanisms responsible for motor disability due to developmental hypoxic injury.